2013
DOI: 10.1259/bjr.20120302
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of pimonidazole-unlabelled intratumour quiescent cell population to γ-rays, accelerated carbon ion beams and boron neutron capture reaction

Abstract: Objective: To detect the radiosensitivity of intratumour quiescent (Q) cells unlabelled with pimonidazole to accelerated carbon ion beams and the boron neutron capture reaction (BNCR). Methods: EL4 tumour-bearing C57BL/J mice received 5-bromo-29-deoxyuridine (BrdU) continuously to label all intratumour proliferating (P) cells. After the administration of pimonidazole, tumours were irradiated with c-rays, accelerated carbon ion beams or reactor neutron beams with the prior administration of a 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It has been previously reported that hypoxic conditions can trigger tumor cells to become quiescent (i.e. not actively dividing), and that these quiescent cells uptake less 10 B-BPA or 10 B-BSH compared with non-quiescent cells [ 25 ]. This negative effect was reported to be stronger with 10 B-BPA than with 10 B-BSH, an observation thought to be due to the fact that 10 B-BSH largely accumulates in cells via diffusion, while 10 B-BPA is actively taken up via LAT1/2 transporters [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that hypoxic conditions can trigger tumor cells to become quiescent (i.e. not actively dividing), and that these quiescent cells uptake less 10 B-BPA or 10 B-BSH compared with non-quiescent cells [ 25 ]. This negative effect was reported to be stronger with 10 B-BPA than with 10 B-BSH, an observation thought to be due to the fact that 10 B-BSH largely accumulates in cells via diffusion, while 10 B-BPA is actively taken up via LAT1/2 transporters [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equally, previous studies have suggested that the ROS/RAC2/P38 MAPK feedback loop is associated with the radio‐resistance of quiescent cells, to 100 kV X‐rays (Pei et al, 2017). Furthermore, following γ‐ray irradiation, the radio‐sensitivity of pimonidazole‐unlabelled quiescent tumour cells (oxygenated cell fraction) was higher than the total cell fraction (quiescent plus proliferating cells; Masunaga et al, 2013). The difference in radio‐sensitivity between the total and quiescent‐cell populations after γ‐ray irradiation was markedly reduced with carbon‐ion beams (290 MeV), especially with a greater LET value (Masunaga et al, 2008).…”
Section: Factors Affecting Dna Repair Efficienciesmentioning
confidence: 99%
“…Interestingly, the very factors that confer radioresistance in cancers cells (i.e. hypoxia and nutrient deprivation) are the very same that promote the growth of CSCs [ 74 - 76 ]. Moreover, it has also been shown that treatment with low dose photons increases the proportion of radioresistant stem cells (radioadaptive resistance) [ 77 , 78 ].…”
Section: Towards the Establishment Of A National Ion Therapy Randd Centmentioning
confidence: 99%
“…Masunaga et al ., showed that a pimonidazole-unlabelled subfraction of quiescent tumor cells, considered the closest representative subpopulation to CSCs, may be a critical target in tumor control [ 76 ]. Treatment with carbon ions were shown to decrease the difference in radiosensitivity between quiescent and non-quiescent cells, as well as, hypoxic and normoxic cells.…”
Section: Towards the Establishment Of A National Ion Therapy Randd Centmentioning
confidence: 99%